Research and improvement of ECG compression algorithm based on EZW. (July 2017) - PENG, Ziran; WANG, Guojun; JIANG, Huabin; MENG, Shuangwu
Highlights: Embedded zerotree wavelet (EZW) is an efficient compression method that has advantages in coding, but its multilayer structure information coding reduces the signal compression ratio. This paper studies the optimization of the EZW compression algorithm and aims to improve it. Lifting wavelet transformation have been used to process electrocardiograph (ECG) signals, focusing on the lifting algorithm. EZW compression coding algorithm were utilized through the ECG information decomposition for feature detection value. Abstract: Embedded zerotree wavelet (EZW) is an efficient compression method that has advantages in coding, but its multilayer structure information coding reduces signal compression ratio. This paper studies the optimization of the EZW compression algorithm and aims to improve it. First, we used lifting wavelet transformation to process electrocardiograph (ECG) signals, focusing on the lifting algorithm. Second, we utilized the EZW compression coding algorithm, through the ECG information decomposition to determine the feature detection value. Then, according to the feature information, we weighted the wavelet coefficients of ECG (through the coefficient as a measure of weight) to achieve the goal of improved compression benefit.